1995
DOI: 10.1046/j.1525-1438.1995.05040310.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between long-term tamoxifen treatment and the development of carcinosarcoma (malignant mixed Müllerian tumor) of the uterus?

Abstract: A cluster of five patients with endometrial carcinosarcoma (malignant mixed Müllerian tumor) occurred at our center during 1993; four of these had been prescribed long-term tamoxifen for breast carcinoma. Searching the archives for the 9-year period 1983-1992 revealed two further cases of uterine carcinosarcoma occurring in patients prescribed tamoxifen, from a total of 16 cases of this tumor. Five of the six patients diagnosed with carcinosarcoma who had been taking tamoxifen had been maintained on the drug f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 3 publications
1
18
0
Order By: Relevance
“…Despite surgical cytoreduction and subsequent chemotherapy being considered the best primary treatment for uterine CS, the overall five-year survival rate is 30 ± 9% for all stages and recurrence is very common (50–80%) [5,6,38]. The characteristics of uterine CS are very different from other types of gynecological cancer, such as ovarian [79,80,81,82,83,84,85], endometrial [86,87], cervical [88,89] and vulvar [90,91] cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite surgical cytoreduction and subsequent chemotherapy being considered the best primary treatment for uterine CS, the overall five-year survival rate is 30 ± 9% for all stages and recurrence is very common (50–80%) [5,6,38]. The characteristics of uterine CS are very different from other types of gynecological cancer, such as ovarian [79,80,81,82,83,84,85], endometrial [86,87], cervical [88,89] and vulvar [90,91] cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In general, uterine sarcoma represents 3–5% of all corpus uteri malignancies, occurring in 1–4 per 1000 women in the USA [4]. CS shares similar risk factors with endometrial carcinomas; both of them are associated with obesity, nulliparity, and the use of exogenous estrogen and tamoxifen [5,6,7]. Conversely, progestin-containing contraceptives are protective against both types of neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…This is, however, controversial, with some studies suggesting that type-2 cancers, such as serous carcinoma, are proportionally more common in association with tamoxifen. 39 40 Indeed, it has been suggested that carcinosarcomas (in reality, metaplastic carcinomas often associated with an epithelial component of type-2 carcinoma 41 42 ) are particularly likely to be associated with tamoxifen, [43][44][45] and adenosarcomas have also been reported. 46 Other studies, however, have found most tamoxifen-associated endometrial neoplasms to be low-grade endometrioid adenocarcinomas.…”
Section: Effects Of Tamoxifen On the Endometriummentioning
confidence: 99%
“…In recent years, there have been occasional reports of uterine carcinosarcoma arising in patients taking tamoxifen for breast cancer (2–7) . The aim of this report is to describe the clinical and pathological findings in 19 patients (two of these have been previously reported (5) ) who developed uterine carcinosarcoma while taking tamoxifen.…”
mentioning
confidence: 99%